Evaluation of ceftazidime/avibactam for serious infections due to multidrug-resistant and extensively drug-resistant Pseudomonas aeruginosa. (December 2018) - Rodríguez-Núñez, Olga; Ripa, Marco; Morata, Laura; de la Calle, Cristina; Cardozo, Celia; Fehér, Csaba; Pellicé, Martina; Valcárcel, Andrea; Puerta-Alcalde, Pedro; Marco, Francesc; García-Vidal, Carolina; del Río, Ana; et al.
Abstract: Objectives: The steady progress in resistance of Pseudomonas aeruginosa (PA) has led to difficulties in treating infections due to multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains. Ceftazidime/avibactam (CAZ/AVI) has in vitro activity against many of these strains, however clinical experience with CAZ/AVI is limited. This study aimed to evaluate the characteristics and outcomes of eight patients with infections due to MDR- or XDR-PA treated with CAZ/AVI, including four strains resistant to ceftolozane/tazobactam. Methods: This was a retrospective descriptive study of patients admitted to a teaching hospital between January 2016 and May 2017 who received CAZ/AVI as initial or continuation therapy for infection due to MDR- and XDR-PA. Results: The sources of infection were hospital-acquired lower respiratory tract infection in five patients (62.5%) and osteomyelitis, meningitis and catheter-related bacteraemia in one patient each. Clinical cure was achieved in 4 patients (50.0%). The 30-day and 90-day mortality rates were 12.5% and 37.5%, respectively. One patient (12.5%) developed encephalopathy that improved with discontinuation of the drug. Conclusions: CAZ/AVI may be a valuable option for serious infections due to resistant PA. Highlights: Infection due to multidrug-resistant (MDR) Pseudomonas aeruginosa is a serious public-health problem worldwide. Newly developed ceftazidime/avibactam is known to be active against a high proportion of MDR and XDR P. aeruginosa . Clinical experience on the potential efficacy of ceftazidime/avibactam in MDR and XDR P. aeruginosa infections is scarce.